(untitled) - Harrison, Bennett (New York, 1994)
This book shows how, in response to international competition, big companies are becoming leaner. Powerful multinational corporations are focusing on their core businesses and contracting out other activities, forming strategic alliances with domestic and foreign partners. Drawing on case studies and empirical research from the United States, Japan, and Europe, Bennett Harrison shows that smaller companies are not responsible for most of the new jobs being created (which may be a good thing, since they pay substantially lower wages and benefits) and are not using, let alone developing, the most up-to-date technologies.
Keywords: Tổ chức lại doanh nghiệp,Corporate reorganizations